Hedonism Life Potrayed The Snows of Kilimanjaro Movie Directed by Henry King - admin, admin (English Language, Linguistics, Literature, And Education Journal, 2024)
Hedonism is a view of life that assumes that people will become happy by seeking as much happiness as possible and avoiding painful feelings whenever possible. Hedonism is a teaching or views that pleasure or pleasure is the purpose of life and human action. Purpose of the research is to explain the types of hedonism portrayed in the Snows Kilimanjaro Movie. In this research, the reseracher used the theory from Daniel Michael Wijers to get the answers from the research. In this reserach, to explain the types of hedonism, the researcher used a descriptive qualitative design by referred to the theories of Creswell (2009) to answer the problem formulated. The approach used in this research is sociology of literature. In collecting data, researcher used techniques documentation. The technique used in analyzing the data in this study is a descriptive technique. The result of this research, there were seven types of hedonism. Folk Hedonism, Value hedonism, Motivational Hedonism, Normative Hedonism, Hedonistic egoism, and Hedonistic UtiIitarism. In this research, the resercher only found two of them, Folk Hedonism and Hedonistic Egoism. For Folk Hedonism, the researcher found 2 data and 5 data for Hedonistic Egoism.